Matematika dalam Dunia Keuangan: Dari Kriptografi Hingga Trading Algoritmik - Perdana, Sigit (Journal of Science and Mathematics Education, 2025)
Mathematics plays a crucial role in the modern financial world, where mathematical concepts are used to model and manage risk, optimize portfolios, and design complex financial instruments. This article discusses various applications of mathematics, ranging from probability theory and statistics to calculus and linear algebra, in the realm of finance. One of its main applications is in cryptography, which involves mathematical techniques to secure digital transactions and personal data. Additionally, mathematics-based trading algorithms, which utilize predictive models and big data analysis, are increasingly used by investors to maximize profits and minimize losses. The article also explores the relationship between option pricing theory and stochastic models used to predict stock price movements. Thus, mathematics not only provides a theoretical foundation but also practical tools that enable financial markets to operate efficiently and securely.